Agreement technologies : 6th International Conference, AT 2018, Bergen, Norway, December 6-7, 2018, Revised selected papers /: 6th International Conference, AT 2018, Bergen, Norway, December 6-7, 2018, Revised selected papers. (2019) - Unknown
No abstract available